Analysis of Innovation and Change in Educational Institutions - Sarta; Ahmad Qurtubi; Anis Fauzi (PT FORMOSA CENDEKIA GLOBAL, 2023)
This article uses the library research approach and is included in qualitative research. Several stages of data presentation are applied in this paper, namely data restatement, description to map data patterns, and interpretation to highlight definite meanings regarding innovation and change in educational institutions. The results of the discussion in this study indicate an action that must be carried out related to innovation. Meanwhile, the causal factors that we ourselves understand are very complex, from innovations to policy changes, developments in science and technology, and the conditions of society.